Pain and itch outcome trajectories differ among European American and African American survivors of major thermal burn injury. Issue 11 (November 2017) - Mauck, Matthew C.; Smith, Jennifer; Shupp, Jeffrey W.; Weaver, Mark A.; Liu, Andrea; Bortsov, Andrey V.; Lateef, Bilal; Jones, Samuel W.; Williams, Felicia; Hwang, James; Karlnoski, Rachel; Smith, David J.; et al.
Abstract : Abstract: More than half of individuals experiencing major thermal burn injury (MThBI) receive an autologous skin graft (autograft), in which skin is removed from a healthy "donor" site and transplanted to the burn site. Persistent pain and itch at the graft site are major causes of suffering and disability in MThBI survivors. African Americans have a higher risk of MThBI, and in other clinical settings African Americans experience a greater burden of pain and itch relative to European Americans. However, to our knowledge, ethnic differences in skin graft site pain and itch outcomes after MThBI have not been assessed. We evaluated skin graft site pain and itch severity (0-10 Numeric Rating Scale [NRS]) over 1 year in a prospective multicenter cohort sample of African Americans and European Americans. In adjusted linear mixed models, African Americans experienced a slower rate of pain resolution in the acute phase of recovery (β = −0.05 vs −0.08 NRS points per day, P < 0.001), which resulted in a higher pain severity in the persistent phase of recovery (NRS mean difference = 1.21, 95% confidence interval [0.12-2.29]), although not statistically significant after correction for multiple comparisons. African Americans also experience greater itch severity in 6 weeks to 12 months after burn injury compared with European Americans (NRS mean difference = 1.86 [0.80-2.93]), which results from a faster rate of itch development in African Americans in the acute recovery phase after burn injury. Future studies may improve outcomes in African Americans and lead to new pathogenic insights that benefit all burn injury survivors. Abstract : Supplemental Digital Content is Available in the Text.A multicenter, prospective study demonstrating differences in pain and itch trajectories between European Americans and African Americans after major thermal burn injury and skin grafting.